Pembiasaan Berdoa Sebelum Belajar Untuk Pendidikan Karakter Siswa Kelas Iv Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis - Isnawati, Isnawati; Peranginangin, Henri; Rahim, Abdur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
In the world of education, the habit of praying is highly recommended to students, especially in Islamic schools such as Madrasah Ibtidaiyah (MI). The purpose of this habituation is to increase spiritual values and religious values for students in family, community, and nation life. Character building in the school environment is very necessary as an educator and activities that support the teaching and learning process that are usually applied are praying before learning. This study aims to determine the habit of praying before studying for the education and character development of fourth grade students of MI Muhammadiyah Sukajati Haurgeulis, and to find out what characters develop from the habit of praying before studying fourth grade students of MI Muhammadiyah Sukajati Haurgeulis. The subjects of this study were fourth grade students, principals, and fourth grade homeroom teachers of MI Muhammadiyah Sukajati Haurgeulis. The research method used is descriptive qualitative research method. Data collection techniques used are interviews, observation, and documentation. Checking the validity of the data is done by means of in-depth observation, document analysis, and triangulation. The results showed: (1) that students became accustomed to leading and memorizing prayers; students become accustomed to applying 5S (Smile, Greet, Greeting, Polite, and Polite); students are trained in giving speeches and accustomed to the practice of praying in congregation; every morning before entering the classroom students pray in lined formation in the field, and (2) from the habit of praying before studying, the students' habits of good character are increasingly embedded, this can be seen from the increase in students' discipline, responsibility, honesty, and courage.